Eutrophication decreases Halophila beccarii plant organic carbon contribution to sequestration potential - Luo, Hongxue; Liu, Songlin; Ren, Yuzheng; Jiang, Zhijian; Wu, Yunchao; Zhang, Xia; Li, Jinlong; Huang, Xiaoping (Frontiers in Marine Science, 2022)
Seagrass ecosystems rank among the most effective blue carbon sinks in climate change mitigation and greenhouse gas removal. Nutrient pollution has emerged as a leading threat to seagrass decline and has diminished the carbon sequestration potential in recent decades. Changes in the nutrient regime can also impact the organic carbon compositions (labile and refractory organic carbon compositions) of seagrass tissues, with important implications for determining the quantity and quality of carbon sequestration. However, there is still little information about the impact of nutrient loading on seagrass plant refractory organic carbon composition (ROC), which hinders our ability to reveal the driving mechanisms of anthropogenic factors that decrease seagrass organic carbon sequestration capability. Here, a multidisciplinary approach was employed to investigate the organic carbon variations of Halophila beccarii at five seagrass meadows with contrasting nutrient loading levels. The results showed that H. beccarii plant nitrogen (N) content ranged from 2.21% to 5.65%, which well reflected the external nutrient loading levels. High nutrient loading elevated labile organic carbon content, like free amino acids and soluble sugars. Nevertheless, ROC content (cellulose-associated organic matter) decreased with increasing nutrient loading, which presented a significant negative linear correlation with plant N content. These results provide evidence that eutrophic conditions enhance H. beccarii plant quality (high N and labile organic carbon) and consequently decrease plant ROC sequestration potential. This suggests that reducing nitrogen input to seagrass meadows would aid in increasing seagrass carbon storage.